SCREENING OF FARNESOL EXTRACTED FROM Syzygium campanulatum LEAF EXTRACT TOWARDS THE GROWTH OF Sf9 CELLS - Lee, Phoebe Pei Han (2018)
Synthetic insecticides are widely used around the world to reduce the occurrence of pests. However, some of them have caused serious problems to human health and environmental pollution. Therefore, many researchers are focusing on finding natural occurring compounds in plants that have insecticidal properties. Syzygium campanulatum is a plant that contains many useful secondary metabolites and is easily found in our country, Malaysia. One of the compounds found in S. campanulatum namely farnesol is a sesquiterpene, which has the ability on insect repellency and believe to have the potential in inhibiting the growth of insect cells. Hence, the aims of this research were to extract and detect the presence of farnesol in S. campanulatum and to study the effect of the extracted farnesol towards the Sf9 cells. Non-polar compounds from S. campanulatum dried leaf powder were extracted using hexane at the ratio of 2:5 (w/v) and the extract was known as crude leaf extract. Crude leaf extract was separated using silica column chromatography and three solvent systems namely hexane, hexane:ethyl acetate (1:1, v/v), and ethyl acetate. The absorbance readings of each column fraction were measured using UV spectrophotometer with a wavelength range from 270 nm to 310 nm. Further separation of crude leaf extract and the column-isolated fraction were performed using TLC to verify the presence of farnesol. Both crude leaf extract and the column-isolated fraction were then subjected to the inhibition of Sf9 cell growth for three incubation durations (24-hr, 48-hr and 72-hr) by measuring A60. Hexane-treated Sf9 cells were used as the positive control in the inhibition study. Hexane was able to extract farnesol based on the presence of one peak identified at 290 nm of the column-chromatogram. Due to the similar peak present in both chromatograms of crude leaf extract and standard farnesol, fraction-14 isolated from crude leaf extract might contain farnesol. Further analysis of TLC results also verified the presence of farnesol spots in both crude leaf extract and fraction-14 when compared to standard farnesol. Hence, both of them were used to inhibit the Sf9 cell growth at three incubation durations. The growth rates for crude leaf extract and fraction-14 at 24-hr were -17.6×10-4 hr-1 and -5.8×10-4 hr-1 respectively. However, the growth rates at 48-hr and 72-hr were remained constant than growth rate at 24-hr which indicated no growth of Sf9 cells at these incubation durations. In conclusions, farnesol was extracted successfully and able to inhibit the growth of Sf9 cells.